Embedded IoT platform for remote traffic control in smart city IoT infrastructure - Nikolskiy, Serhiy; Klymenko, Iryna (Видавництво Львівської політехніки, 2023)
A justified hybrid multilevel approach to IoT infrastructure implementation is set to facilitate the achievement of a scalable IoT (Internet of Things) infrastructure, incorporating integration into cloud technologies and services. The localization of hardware-software traffic management means at the lower level of the IoT infrastructure, close to data collection devices, ensures the generation of control influences in real-time, and relieves communication channels at the higher levels of the IoT infrastructure architecture. A technology for generating control influences for remote traffic management is proposed, which is based on the developed AT command system for deploying a web server and generating web pages using the capabilities of the embedded IoT platform on modern microcontrollers. The proposed technology allows for the formation of control influences in real-time, in an easily comprehensible textual format, using a web interface in the local domain of the IoT infrastructure. It also enables the visualization of information on remote displays and information boards, as well as on displays integrated into automotive equipment. The proposed technology can be used to inform road traffic participants about critical situations and can be embedded in smart traffic lights within remote traffic management systems or used to implement virtual traffic lights.
Keywords: Embedded systems; Internet of Things; Edge Computing; Microcontroller Units; Remote control; Traffic control; Smart City